Functions of senses in learning - Sancak Sert, Zeynep; Panieri, Giuliana; Peftieva, Olena (Septentrio Educational, 2023)
Using various senses to process and store new information is a powerful way of exploring the natural environment for children, but also adults. Using senses through the sensory organs (the eyes, ears, nose, tongue, and skin) makes the learning experience effective, meaningful and unforgettable. This is the most natural method that children use to learn each detail in their environment since they were born.